2021
DOI: 10.2147/jir.s299927
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Activation Mediates Noradrenergic Locus Coeruleus Neurodegeneration via Complement Receptor 3 in a Rotenone-Induced Parkinson’s Disease Mouse Model

Abstract: Background Chronic exposure to the insecticide rotenone can damage dopaminergic neurons and lead to an increased risk of Parkinson’s disease (PD). Whereas it is not clear whether rotenone induces neurodegeneration of noradrenergic locus coeruleus (LC/NE) neurons. Chronic neuroinflammation mediated by microglia has been involved in the pathogenesis of PD. Evidence shows that complement receptor 3 (CR3) is a crucial regulator of microglial activation and related neurodegeneration. However, it is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…However, controversial effects of microglia have been reported in MPTP‐, 6‐OHDA‐ or rotenone‐induced PD models. 18 , 22 , 23 , 24 To clarify the function of microglia in Parkinson's disease, in this study, we fed mice with a PLX3397‐containing diet for different days to test the efficiency of microglial depletion in the nigrostriatal pathway. Our data reveal that 21‐day treatment with PLX3397 dramatically reduced the microglial population in the substantia nigra, and had no noticeable effect on the nigrostriatal dopaminergic pathway in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controversial effects of microglia have been reported in MPTP‐, 6‐OHDA‐ or rotenone‐induced PD models. 18 , 22 , 23 , 24 To clarify the function of microglia in Parkinson's disease, in this study, we fed mice with a PLX3397‐containing diet for different days to test the efficiency of microglial depletion in the nigrostriatal pathway. Our data reveal that 21‐day treatment with PLX3397 dramatically reduced the microglial population in the substantia nigra, and had no noticeable effect on the nigrostriatal dopaminergic pathway in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Moreover, in rotenone‐induced mouse PD models, microglial activation contributed to neurodegeneration in the locus coeruleus and cognitive impairments. 23 , 24 Thus, whether microglia are beneficial or harmful remains controversial in PD. And the effects of repopulated microglia in PD are also warranted to illustrate.…”
Section: Introductionmentioning
confidence: 99%
“…Adult male C57BL/6 mice were randomly separated into control, 0.75 mg/kg/d and 1.5 mg/kg/d rotenone groups ( n = 12). Rotenone was administered to mice by intraperitoneal injection for three consecutive weeks [ 18 , 19 ]. Control mice received equal amounts of vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Rotenone at a dose of 1.5 mg/kg/d was administered as described above. Mice in the rotenone + PLX3397 group received (by gavage, daily) PLX3397 (40 mg/kg/d), a selective antagonist for CSF1R, for 7 days and then were treated every other day 30 min prior to rotenone until the end of the experiment [ 18 , 19 ]. Mice in the rotenone + minocycline group received (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a colony stimulating factor 1 receptor (CSF1R) inhibitor, PLX5622, was developed to deplete >95% of all microglia in the central nervous system. 37 In Alzheimer's disease (AD), several groups have identified that PLX5622 could improve cognition in 3xTg-AD, APP-PS1 transgenic and 5xFAD mice model. [38][39][40][41] In traumatic brain injury (TBI), recent studies also have reported that PLX5622 treatment limited TBIassociated neuropathology.…”
Section: Discussionmentioning
confidence: 99%